The Influence of Superior Leadership Competency on The Achievement of Key Performance Indicators of SOE Banks - Purwadi, Aryanto; Sinaga, Bonar M; Sukmawati, Anggraini; Denni, Alex (School of Business, Bogor Agricultural University (SB-IPB), 2022)
This research examines the effect of superior leadership competence in achieving key performance indicator (KPI) Bank XYZ as a State Own Enterprise (SOE). The number of respondents was 318, and the data was processed using Structural Equitation Modeling (SEM) Lisrel 8.80 model 1. The results supported the hypothesis that (1) leading business competence affects superior leadership, and it is acceptable; (2) competence of leading people and organizations influencing superior leadership is acceptable; and (3) superior leadership influences achievement of KPI, which is acceptable. In contrast, superior leadership is determined by transformational and transactional leadership variables. The dimension of transformational leadership that received the highest of scores 5 (strongly agree) from employee was inspirational motivation. Leaders motivate and inspire employees by speaking optimistically about the company's future, speaking enthusiastically about what the company needs to achieve, articulating an achievable vision for the future, as well as convincing and expressing confidence in the goal. Keywords: leading business competence, leading people and organization competence, superior leadership, transformational leadership, transactional leadership